Topological Orbit Equivalence Classes and Numeration Scales of Logistic Maps - Cortez-Munoz, M (2012)
We show that every uniquely ergodic minimal Cantor system is topologically orbit equivalent to the natural extension of a numeration scale associated to a logistic map. © Copyright Cambridge University Press 2011.